Analysis of disability indicators due to occupational diseases in the Lviv region: problems and perspectives of the decision. - I. Borisova; V. Reshota; Z. Nikolishin (Medičnì Perspektivi)
Disability is a social phenomenon that can not be ruled out by any society. The potential of society in combating the growth of disability – as a social evil – is determined not only by the degree of understanding of this problem but mainly by economic resources. The risk of developing occupational diseases in the coal industry is 5-10 times higher than in other branches of industry. In Ukraine, about 3 million people work under the harmful conditions of production, 60.0% of them are miners. The study analyzed the dynamics of disability as a result of occupational diseases in the Lviv region for the period 2015-2017. The results of the study prove that the disability indicators due to occupational diseases tend to grow. The ways to overcome this unfavorable tendency should be state measures on improvement of normative and legal documents, coherence between different state institutions and strengthening effective state control over hygiene norms in industries with harmful factors.